Study of HPGe detector shielding for use in inelastic neutron scattering experiments at the n_TOF/CERN facility - Papanikolaou, Dimitris (HNPS Advances in Nuclear Physics, 2023)
The study of inelastic scattering reactions is important both in basic research as it can provide an insight on nuclear structure and aid in the validation of theoretical models, as well as in the field of applications. The most frequently used method to determine the neutron induced inelastic scattering cross section is by recording the emitted gamma rays from the de-excitation of the target nucleus. In this direction, the high energy resolution of the HPGe detectors is instrumental. The experimental setup can be further improved by shielding the HPGe against the scattered neutrons. The purpose of this work is to investigate the contribution of such shieldings used in inelastic neutron scattering experiments at the n_TOF facility at CERN and to optimise the experimental set-up. In this study, GEANT4, a package for simulating the transport of radiation through matter, was used to study the effect of the various shielding materials and geometries for CANBERRA’s EGPC 25S/N 540 p-type coaxial prototype HPGe.